Compllete handyman do-it-yourself encyclopedia : a complilation of special interest projects and manual for the repair and care of homes, autos, appliances, hobby equiipment. XXI. wind gauge-index (H.S. Stuttman Co, 1975)
3.087-3.240 p.; 25 cm.